LANGUAGE BARRIERS: A CASE STUDY ON ENGLISH TEACHING PROCESS TOWARDS STUDENTS’ LEARNING THE LANGUAGE AT SMP NEGERI MOLIBAGU - Gobel, Meylirda Dewi; Malik, Harto; Luwiti, Sri Rumiyatiningsih (Pascasarjana, Universitas Negeri Gorontalo, 2024)
This research explores the challenges faced by English teachers in secondary schools, focusing on language barriers and strategies to overcome them. In Indonesia, where English proficiency is limited outside of academic settings, students often struggle with effective communication and participation in English classes. Qualitative methods, including interviews and observations at SMP Negeri Molibagu, were employed to gather insights directly from teachers. Teachers at SMP Negeri Molibagu encounter obstacles such as student proficiency limitations, inadequate teaching materials, and restricted instructional time, impacting their delivery of effective English lessons. To address these challenges, teachers employ strategies such as adapting teaching materials, integrating technology, and fostering collaborative learning environments. These efforts aim to enhance student engagement and comprehension despite language barriers. Thematic analysis of interview and observation data reveals recurring patterns in teachers' experiences and practices, emphasizing the adaptation of teaching methods, collaborative efforts to supplement resources, and strategies to boost student confidence and motivation in English learning. By addressing these challenges, this study offers practical insights for educators and policymakers aiming to improve English language instruction in Indonesia, advocating for tailored strategies that support diverse student needs and promote inclusive learning environments.Â